2008
DOI: 10.1007/s11695-008-9673-x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Routine Preoperative Upper GI Endoscopy: Why All Patients Should Be Evaluated?

Abstract: Routine preoperative endoscopy detects different abnormalities which need specific approach prior to surgery. Preoperative endoscopy should be performed to all patients prior to surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(38 citation statements)
references
References 25 publications
3
34
1
Order By: Relevance
“…Muñoz et al (26) diagnosed UGI abnormalities in 46% in the obese patients, one of them with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Muñoz et al (26) diagnosed UGI abnormalities in 46% in the obese patients, one of them with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for performing UGI in the candidates to bariatric surgery is to detect and treat lesions that might potentially lead to complications in the immediate postoperative period, or result in diseases in the months or years following RYGBP surgery (25,26) . Eradication of the H. pylori as a routine in the preoperative of bariatric surgery is still debated and scarce researches were performed in regards the histology of gastric mucosa (2,7,11,23,25,26,30,33,34,35) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to World Health Organization estimation, there are over 500 million obese adults [BMI (body mass index)>30 kg/m 2 ] across the world (1). Obesity is known to increase susceptibility to several conditions including type 2 diabetes mellitus (DM), hypertension (HTN), dyslipidemia, coronary artery disease, some cancers, sleep apnea syndrome, gastroesophageal reflux disease (GERD) and esophageal motility disorders (2,3). Initial treatment of obesity includes diet, life-style changes, exercise and some medicines, but given the long-term outcomes, effective treatment appears to be achieved by bariatric surgery (4).…”
Section: Introductionmentioning
confidence: 99%
“…However, the rationale for using routine endoscopy in asymptomatic patients before bariatric surgery remains contentious [3][4][5][6][7][8][9][10]. Several authors have now documented the lack of correlation between patient symptoms and endoscopic findings and have suggested that routine preoperative endoscopy might in fact be useful in detecting both lesions and inflammation [11,12]. Besides, there is no long-term data available after sleeve gastrectomy, reflux esophagitis and/or hiatal hernia may contraindicate this operation, especially since the absence of preoperative symptoms cannot be relied upon.…”
Section: Introductionmentioning
confidence: 99%